The challenges of community-based natural resource management in pastoral rangelands - Robinson, Lance W.; Eba, Bedasa; Flintan, Fiona E.; Frija, Aymen; Ng'ang'a, Irene N.; Ontiri, Enoch M.; Sghaier, Mongi; Abdu, Nizam H.; Moiko, Stephen S. (Informa UK Limited, 2021)
Recognizing that community-based natural resource management (CBNRM) approaches have had mixed success in pastoral rangelands, this paper compares five case studies—two from Kenya, two from Ethiopia and one from Tunisia—to identify aspects of social-ecological context that affect the implementation and success of CBNRM in pastoral settings. Data for each case was collected following a common protocol. Among the characteristics that emerged from our study as important were socio-political and biophysical characteristics of the wider landscape within which the community’s rangeland territory is located and the extent to which that territory is circumscribed by some combination of other land uses and land tenure types, major political boundaries, and physical landscape features. The analysis of these cases suggests that where pastoralist communities coexist in large, open rangeland landscapes, rather than a narrowly community-based approach, natural resource management interventions need to be explicitly multi-level and horizontally flexible.